2020
DOI: 10.33549/physiolres.934528
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Egocentric and Allocentric Reference Frames in Static and Dynamic Conditions in Humans

Abstract: The dissociation between egocentric and allocentric reference frames is well established. Spatial coding relative to oneself has been associated with a brain network distinct from spatial coding using a cognitive map independently of the actual position. These differences were, however, revealed by a variety of tasks from both static conditions, using a series of images, and dynamic conditions, using movements through space. We aimed to clarify how these paradigms correspond to each other concerning the neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In our iEEG study, we did not find any allocentric-selective channels in the PPA and medial occipitotemporal cortex more generally, although an fMRI (Committeri et al 2004 ) and another follow-up iEEG study (Bastin et al 2013 ) showed posterior parahippocampal involvement during the allocentric task. Possibly, medial occipitotemporal cortex, including PPA, is only involved in the world-centered allocentric RF use and may reflect the coding of the current spatial relationships between the viewer and the whole environmental geometry (see reviews Galati et al 2010 and Moraresku and Vlcek 2020 ). In contrast, the LTC seems to be associated with object-centered RF, as our experimental design included the object-centered allocentric condition in which the subjects did not need to focus on the whole environmental geometry but rather on the local spatial relationships between objects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our iEEG study, we did not find any allocentric-selective channels in the PPA and medial occipitotemporal cortex more generally, although an fMRI (Committeri et al 2004 ) and another follow-up iEEG study (Bastin et al 2013 ) showed posterior parahippocampal involvement during the allocentric task. Possibly, medial occipitotemporal cortex, including PPA, is only involved in the world-centered allocentric RF use and may reflect the coding of the current spatial relationships between the viewer and the whole environmental geometry (see reviews Galati et al 2010 and Moraresku and Vlcek 2020 ). In contrast, the LTC seems to be associated with object-centered RF, as our experimental design included the object-centered allocentric condition in which the subjects did not need to focus on the whole environmental geometry but rather on the local spatial relationships between objects.…”
Section: Discussionmentioning
confidence: 99%
“…A series of fMRI studies investigated neural correlates of allocentric and egocentric RFs during spatial judgment and navigation tasks and showed the involvement of separate brain areas for two types of spatial coding. Specifically, egocentric RF use was accompanied by dominant activity in the superior parietal lobule, precuneus, superior, middle and inferior frontal gyri (Committeri et al 2004 ; Galati et al 2000 ; Parslow et al 2004 ; Rosenbaum et al 2004 ; Ruotolo et al 2019 ; Saj et al 2014 ), while allocentric RF use was supported by activation in the lateral and ventromedial occipito-temporal cortex (Committeri et al 2004 ; Galati et al 2000 ; Ruotolo et al 2019 ; Saj et al 2014 ), and also in the hippocampus in spatial navigation studies (Hirshhorn et al 2012 ; Iaria et al 2007 ; Jordan et al 2004 ; Maguire et al 1998 ; Rodriguez 2010 ; Spiers and Maguire 2007 ; see also review Moraresku and Vlcek 2020 ). Egocentric and allocentric coding are tightly connected with spatial attentional control, which in the healthy brain has been linked to the activation of a distributed frontoparietal attention network (Corbetta and Shulman 2002 ; Szczepanski et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, common brain regions, including the frontal, central, parietal, and occipital cortex, were explored during active navigation for both egocentric and allocentric using an egocentric or an allocentric reference frame, respectively. Our successful navigation involved significant EEG modulation power changes that were dominant in the theta (4-7 Hz), alpha (8-14 Hz), and beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency bands between widespread brain regions.…”
Section: B Eeg Dynamics With Distinct Reference Frames In Spatial Navigationmentioning
confidence: 99%
“…As an excellent tool to create equal real-world environment, Delaux and his colleagues studied simultaneous brain/body imaging during navigation in mobile conditions with virtual Y-maze by using the VR environment [12]. For spatial reference frames on diverse conditions of spatial navigation, Moraresku and Vlcek investigated brain activation during different reference frames used in previous VR environment-based studies [19]. Moreover, using a novel, fully mobile virtual reality paradigm, Plank and his colleagues studied the EEG correlates of spatial reference frames formed during unsupervised exploration [11].…”
mentioning
confidence: 99%
“…In the allocentric approach, the object represented has an origin and a reference direction. The reference is independent of the observer and depends on the relations between objects and their spatial positions (Klatzky, 1998;Moraresku and Vlcek, 2020).…”
mentioning
confidence: 99%